2021
DOI: 10.1080/03079457.2021.1872766
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of fowl adenovirus (FAdV) infections in South Korean chickens during 2013–2019 following introduction of FAdV-4 vaccines

Abstract: Fowl adenoviruses (FAdV) are important infectious pathogens responsible for causing substantial economic losses to the poultry industry worldwide. One hundred and forty-six FAdV strains were continuously collected and analysed from 2013 to 2019 to understand the epidemiological change and nature of the virus in South Korea from two different standpoints, before and after the release of multiple commercial FAdV-4 vaccines. Phylogenetic analysis of the hexon loop-1 gene sequences showed that 92 strains belonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…The results demonstrated that the mono-serotype FAdV-4 vaccine could provide broad cross-protection against all five serotypes of FAdVs used in this study, not only in vaccinated chickens but also in their progenies with confirmed maternally derived antibodies. The coordinated efforts by the research and industry sectors to control FAdV-4 outbreaks through vaccination programs were fortunately fruitful at some level, as cases involving this serotype started to decline rapidly in 2017 [45].…”
Section: Development Of Domestic Fadv Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…The results demonstrated that the mono-serotype FAdV-4 vaccine could provide broad cross-protection against all five serotypes of FAdVs used in this study, not only in vaccinated chickens but also in their progenies with confirmed maternally derived antibodies. The coordinated efforts by the research and industry sectors to control FAdV-4 outbreaks through vaccination programs were fortunately fruitful at some level, as cases involving this serotype started to decline rapidly in 2017 [45].…”
Section: Development Of Domestic Fadv Vaccinesmentioning
confidence: 99%
“…There has been an increase in reports of HHS and IBH outbreaks from various regions in the last ten years, such as in Europe [41][42][43][44], Asia [45][46][47][48][49], Oceania [30], North America [50], South America [51,52], and Africa [53,54], indicating even geographical spread of FAdVs. As in most Asian countries, FAdV-induced outbreaks in poultry have been observed in South Korea for many years, and, to date, these outbreaks persist.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although heterologous protection in FAdV-causing IBH is still under debate [1,6], previous experimental studies suggest that FAdV-4 inactivated vaccines could provide broad cross-protection against various serotypes of FAdV, not only in vaccinated breeders but also in their progenies [3,26], in line with our findings. However, the crossprotective efficacy of FAdV-4 vaccines in the field has yielded conflicting results; while a field study in China suggests that FAdV-4 inactivated vaccine successfully controlled FAdV-11 [27], its application in South Korea caused an increase of FAdV-11 cases [28], and no cross-protection against FAdV-8b was observed in either country [27,28]. Thus, the complete absence of FAdV-11 in breeders in 2012-2013 provides a strong field evidence for cross-protection by the inactivated vaccine containing FAdV-4.…”
Section: Discussionmentioning
confidence: 99%
“…Avian adenovirus (6/E, 7/E and 8/E) have been reported to cause IBH in Australia and New Zealand. Saudi Arabia investigated type/species 2/D and 6/E, and newly shifted from 4/C to 8b/E strains indicated in South Korea [ 37 ] and other parts of the world [ 12 , 16 ]. Additionally, researchers from India have reported the presence of avian adenoviruses such as 2/D, 5/B, 6/E, 7/E and 12/D in addition to type/species 4/C and 8/E [ 38 ].…”
Section: Introductionmentioning
confidence: 99%